Self-Assessment of Adherence to Medication: A Case Study in Campania Region Community-Dwelling Population - Enrica Menditto; Francesca Guerriero; Valentina Orlando; Catherine Crola; Carolina Di Somma; Maddalena Illario; Donald E. Morisky; Annamaria Colao (Journal of Aging Research)
Objectives. The aim of the study was to assess self-reported medication adherence measure in patients selected during a health education and health promotion focused event held in the Campania region. The study also assessed sociodemographic determinants of adherence. Methods. An interviewer assisted survey was conducted to assess adherence using the Italian version of the 8-item Morisky Medication Adherence Scale (MMAS-8). Participants older than 18 years were interviewed by pharmacists while waiting for free-medical checkup. Results. A total of 312 participants were interviewed during the Health Campus event. A total of 187 (59.9%) had low adherence to medications. Pearson’s bivariate correlation showed positive association between the MMAS-8 score and gender, educational level and smoking (P<0.05). A multivariable analysis showed that the level of education and smoking were independent predictors of adherence. Individuals with an average level of education (odds ratio (OR), 2.21, 95% confidence interval (CI), 1.08–4.52) and nonsmoker (odds ratio (OR) 1.87, 95% confidence interval (CI), 1.04–3.35) were found to be more adherent to medication than those with a lower level of education and smoking. Conclusion. The analysis showed very low prescription adherence levels in the interviewed population. The level of education was a relevant predictor associated with that result.